Analyzing the Implementation of Policies and Guidelines for the Prevention and Management of Type 2 Diabetes at Primary Health Care Level in Nepal - Shrestha, Rabina; Yadav, Uday Narayan; Shrestha, Abha; Paudel, Grish; Makaju, Deepa; Poudel, Prakash; Iwashita, Hanako; Harada, Yuriko; Shrestha, Archana; Karmacharya, Biraj; Koju, Rajendra; Sugishita, Tomohiko; et al. (Frontiers in Public Health, 2022)
Background: This study reviewed diabetes related existing policies and its implementation process at the primary health care level in Nepal. Methods: This study involved two phases: Phase I: situation analyses through review of documents and Phase II: qualitative exploratory study. In phase I, four databases (Medline, Web of Science, Embase and PubMed) were systematically searched using key search terms related to diabetes care and policies between January 2000 to June 2021. Also, relevant gray literature was reviewed to understand the trajectory of policy development and its translation with regards to diabetes prevention and management at primary health care level in Nepal. Following the phase I, we conducted qualitative interviews with health care providers, policy makers and managers (in-depth interviews =13, and key-informant interviews =7) at peripheral and central levels in Kavrepalanchowk and Nuwakot districts of Nepal. Results: Four key themes were identified including (i) limited implementation of policies into practices; (ii) lack of coordination among the different level of service providers; (iii) lack of trained human resources for health and inadequate quality services at the primary health care level, and (iv) inadequate access and utilization of diabetes care services at primary health care level. Specifically, this study identified some key pertinent challenges to the implementation of policies and programs including inadequate resources; limited engagement of stakeholders in service design and delivery; trained health care providers; lack of financial resources to strengthen peripheral health services; fragmented health governance and weak reporting and monitoring systems. Conclusion: This study revealed that the policies, plans and strategies for prevention and management of NCDs in Nepal recognised importance of diabetes prevention and control. However, a major gap remains with adequate and lack of clarity in terms of implementation of available policies, plans, strategies and programs to address the problem of diabetes. We suggest the need for multi-sectoral approach (engaging both health and non-health sectors) at central as well as peripheral levels to strengthen the policies implementation process; building capacity of health care providers; ensuring adequate financial and non-financial resources and improving quality of services at primary health care levels.